2012
DOI: 10.1111/j.1530-0277.2012.01773.x
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol Attenuates the Progression of Alcohol Fatty Liver Disease in Rats

Abstract: Ethanol metabolism-induced lipogenesis may trigger the SNS-activated HSCs feedback loop, and then induct the activated HSCs and the activated HSCs-derived TNF-α, the mediator of lipogenesis, overproduction. Carvedilol may block this feedback loop via antisympathetic activity and demonstrate its preventive role on the development of hepatosteatosis in rat with AFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
3
25
3
Order By: Relevance
“…Studies have reported that chronic alcohol consumption induced liver injury associated with sympathetic hyperactivity, and implicated ROS in the pathogenesis of activation of the SNS, which may affect liver injury by modulating cellular oxidative damage . The major source of ROS is nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, an enzyme that can be activated during ethanol metabolism, leading to the production of superoxide anions (O – 2 ) in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that chronic alcohol consumption induced liver injury associated with sympathetic hyperactivity, and implicated ROS in the pathogenesis of activation of the SNS, which may affect liver injury by modulating cellular oxidative damage . The major source of ROS is nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, an enzyme that can be activated during ethanol metabolism, leading to the production of superoxide anions (O – 2 ) in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were housed at constant temperature (22 ± 2°C) and humidity (45 ± 5%), and exposed to a standard light : dark cycle (12:12 h) at the Institute of Laboratory Animals, Yamaguchi University. The same ethanol consumption protocol was used as in our previous liver study . In brief, 52 rats were housed individually, assigned to a group randomly, and fed a nutritionally adequate liquid diet for 49 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the SNS may contribute at least partly to the sensitizing effect of ethanol on lipopolysaccharide-induced liver injury in mice and concurrent administration of the beta-blocker propranolol with ethanol results in attenuation of this effect [62]. Carvedilol, an agent, which can block the SNS completely via b1, b2, and a1 adrenergic receptors, may have a protective role against development of hepatosteatosis in rats with alcohol fatty liver disease [63]. On the other hand, hepatic sympathetic innervation is protective against Fas-mediated fulminant hepatitis.…”
Section: Liver Innervation In Diseasementioning
confidence: 96%
“…CVD provides greater cardiovascular benefits than traditional β-blockers that have been attributed to its antioxidant, anti-inflammatory, and anti-fibrotic properties [9]. The anti-fibrotic effects of CVD have been associated with the amelioration of oxidative stress in carbon tetrachloride-induced hepatotoxicity model [10] and suppression of hepatic satellite cell-derived lipogenesis-and fibrogenesis-related mediators [11].…”
Section: Introductionmentioning
confidence: 99%